Robust inference for non‐linear regression models from the Tsallis score: Application to coronavirus disease 2019 contagion in Italy. Issue 1 (23rd October 2020) - Girardi, Paolo; Greco, Luca; Mameli, Valentina; Musio, Monica; Racugno, Walter; Ruli, Erlis; Ventura, Laura
Abstract : We discuss an approach of robust fitting on non‐linear regression models, in both frequentist and Bayesian approaches, which can be employed to model and predict the contagion dynamics of the coronavirus disease 2019 (COVID‐19) in Italy. The focus is on the analysis of epidemic data using robust dose–response curves, but the functionality is applicable to arbitrary non‐linear regression models.